Public debt and economic growth: empirical evidence from South Africa - Mbali, Andiswa (Graduate School of Business (GSB), 2022)
This study seeks to investigate the relationship between public debt and economic growth in South Africa for the period 1977 – 2019. This study also seeks to review economic theories related to public debt and economic growth namely: Neoclassical, Ricardian and Keynesian theory. To achieve the research objective, this study uses the time series technique, namely, the autoregressive distributed lag (ARDL) bounds testing approach of cointegration test and the Granger causality approach to test the causal relationship between variables. Analysis of variance decomposition and impulse response functions are used to illustrate the proportions of movements of variables due to its own shock relative to other variables by shocking one standard deviation. The study results indicate there is a positive relationship between public debt and economic growth . However, causality runs from economic growth to public debt. Overall, the study results indicate a significant negative long-run relationship between the public debt and economic growth when inflation and gross capital formation are used as controlled variables. However, the relationship is significant in the short run. The impulse response function indicated that there is responsiveness in public debt and GDP growth to shocks of public debt and GDP growth. However, the result of variance decomposition test in explaining the GDP growth and public debt co-movement. In the short run, self-variance of GDP growth comovement is almost 100%, which reduces to 91.79% percent in the long term. Aside from selfvariation, public debt induced no notable variation in bilateral co-movement in short term. In the long-run however, maximum variation of 8.22% is provided by public debt. The above statistics suggest that shock in economic growth accounts for 91.78% fluctuations. A shock to public debt causes fluctuations to GDP growth significantly over time. Last, as a policy recommendation, South Africa needs undertake aggressive economic strategies with clear objectives and strong commitments, driven by accountable bureaucrats to ensure that public funds are used efficiently. Public debt also needs to be directed through economic growth driven projects and productive expenditures.